007 Functional neurological disorders and sociodemographic factors: a review. Issue 9 (12th August 2022) - Vidot, Micha; Wu, Kit; Mitchell, James; Nitkunan, Arani; Carr, Georgina
Abstract : Background: To improve equity of service, in line with the aspirations of public policy across the UK, it is imperative that we understand how sociodemographic factors affect the management and care of functional neurological disorders (FND). Aims: To describe the relationship between sociodemographic factors and the epidemiology, clinical factors, diagnosis, treatment, patient experience and outcomes for people with FND. Methods: We conducted a focused review of published literature from 2000 to 2021 investigating the rela- tionship between FND and each of the patient protected characteristics, as outlined in the Equality Act 2010, with additional factors such as socioeconomic status, education and employment also included. Results: There is limited but some published data looking at age, disability, marriage/civil partnership, race, sex and gender, education and employment. However, minimal data is found discussing gender reassignment, pregnancy and maternity, religion and beliefs, sexual orientation, geographical variation, socioeconomic status and settlement status/immigrants. Discussion: FND is a relatively new term used to describe a condition that has had many aliases in the past, therefore leading to a lack of consistency in terminology and research methodology. Further research is needed to explore FND in relation to patient protected characteristics, and the effect on patient outcomes.